2017
DOI: 10.1080/13625187.2016.1276162
|View full text |Cite
|
Sign up to set email alerts
|

The legal and non-legal barriers to abortion access in Australia: a review of the evidence

Abstract: Although this review can form a base for the national improvement of abortion access, the gap found in Australian research demonstrates a need for additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…One national study found that 18% of women traveled more than 100 km (62 miles) to reach an abortion clinic and that younger woman and Aboriginal women traveled significantly further for services than older and white women [12]. A review of studies examining barriers to abortion access in Australia found that interstate travel for abortion was common, rural access to abortion was limited, and that greater travel distances were associated with greater costs [13]. In New Zealand, a study of access to first trimester abortion found that women in regions without an abortion provider had to travel on average 137 miles each way to reach abortion services, and that regions without a provider had higher than average native (Maori) populations [14].…”
Section: Introductionmentioning
confidence: 99%
“…One national study found that 18% of women traveled more than 100 km (62 miles) to reach an abortion clinic and that younger woman and Aboriginal women traveled significantly further for services than older and white women [12]. A review of studies examining barriers to abortion access in Australia found that interstate travel for abortion was common, rural access to abortion was limited, and that greater travel distances were associated with greater costs [13]. In New Zealand, a study of access to first trimester abortion found that women in regions without an abortion provider had to travel on average 137 miles each way to reach abortion services, and that regions without a provider had higher than average native (Maori) populations [14].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of MA knowledge, awareness and provision, among this presumably pro‐abortion sample, indicates a need for improved abortion education in the curricula of medical and nurse students and for interventions that focus on the benefits, safety and feasibility of MA provision. Education also needs to address the perceived uncertainty regarding the legal restrictions involved with the provision of MA in Victoria, as the complex mix of inconsistent abortion laws across Australia might discourage those considering providing MA services …”
Section: Discussionmentioning
confidence: 99%
“…Access to abortion services in Australia is not without barriers. The legal differences and ambiguities in abortion laws across Australian jurisdictions, together with anti‐abortion views and the fear of stigma or harassment, can affect the willingness of doctors to provide abortions . Abortion provision remains predominantly confined to private clinics in metropolitan areas, and abortion access for women from Australia's regional and rural areas can therefore be highly restricted .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, women who were hospitalized for an “abortion” that was not induced for legal reasons were 3.5 times more likely to receive contraceptive methods. Counseling about starting contraceptives to prevent a new pregnancy for women who have had a legal abortion induction can be difficult . Induced abortion in Brazil has restrictive laws and is associated with a moral stigma, which creates an obstacle to improving health care and hinders both practical actions and social and cultural aspects related to women's health problems.…”
Section: Discussionmentioning
confidence: 99%